Pengaruh Pelaksanaan Gerakan Literasi Sekolah Dan Pemanfaatan Teknologi Informasi Dalam Pembelajaranterhadap Mutu Pendidikan Di Sekolah Dasar Negeri Kecamatan Labuapi - Zuraeda, Zuraeda; Sukardi, Sukardi; Syafruddin, Syafruddin (Primera Educatia Mandalika: Elementary Education Journal, 2024)
Student learning outcomes must be a serious concern so that various efforts can be made to improve them. One of them is by increasing school literacy and utilizing information technology in learning. This research aims to examine the influence of the implementation of the school literacy movement and the use of information technology in learning on the quality of education. In this research, the approach used is a quantitative descriptive approach with a comparative causal research method. The sample in this study consisted of 83 teachers in ten State Elementary Schools in Labuapi District. The data in this research was obtained using a questionnaire. The statement format in the questionnaire has answer choices given a score of 1-4 based on a Likert scale. After the data was obtained, the results were presented descriptively and processed for hypothesis testing with multiple linear regression, T test, and F test using SPSS version 25. The research results showed that the School Literacy Movement positively and significantly affected the Quality of Education. Information Technology has a positive and significant effect on the Quality of Education. The School Literacy Movement and the Use of Information Technology significantly affect the Quality of Education in Labuapi District State Primary Schools.